Macroeconomic Shocks and Racial Labour Market Differences in the U.S. - Kuhelika De; Ryan A. Compton; Daniel C. Giedeman; Gary A. Hoover (Center for Economic Studies and ifo Institute (CESifo), 2019)
Using 136 United States macroeconomic indicators from 1973 to 2017, and a factor augmented vector autoregression (FAVAR) framework with sign restrictions, we investigate the effects of three structural macroeconomic shocks - monetary, demand, and supply – on the labour market outcomes of black and white Americans. Our results indicate that adverse macroeconomic shocks have differential effects on labour market outcomes for blacks and whites, hurting blacks disproportionately relative to whites. Black Americans appear to be significantly more sensitive to macroeconomic shocks than white Americans. Evidence from our FAVAR model, which uses information on contractionary initiatives by the Federal Reserve, indicates that the employment-population ratio among black Americans falls close to twice as much as that among white Americans, primarily due to an increase in their unemployment rate and not a decline in labour force participation rate. Policymakers should take account of these heterogeneous effects across racial groups when implementing disinflationary guiding policy.
Keywords: C32; E24; E32; E52; J10; J15; 330; macroeconomic shocks; monetary policy; business cycles; labour market; unemployment; racial inequality; FAVAR; sign restrictions